2007
DOI: 10.1038/nm1653
|View full text |Cite
|
Sign up to set email alerts
|

Classification and prediction of clinical Alzheimer's diagnosis based on plasma signaling proteins

Abstract: A molecular test for Alzheimer's disease could lead to better treatment and therapies. We found 18 signaling proteins in blood plasma that can be used to classify blinded samples from Alzheimer's and control subjects with close to 90% accuracy and to identify patients who had mild cognitive impairment that progressed to Alzheimer's disease 2-6 years later. Biological analysis of the 18 proteins points to systemic dysregulation of hematopoiesis, immune responses, apoptosis and neuronal support in presymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
809
11
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 965 publications
(850 citation statements)
references
References 13 publications
20
809
11
10
Order By: Relevance
“…A recent study examining plasma signaling proteins as predictors of AD diagnosis suggested changes in blood may be representative of structural and metabolic changes in the brain, and specific to AD [27]. We have a similar hypothesis for SM and ceramides because the homeostasis of these lipids are critical to both the brain and periphery.…”
Section: Discussionmentioning
confidence: 59%
“…A recent study examining plasma signaling proteins as predictors of AD diagnosis suggested changes in blood may be representative of structural and metabolic changes in the brain, and specific to AD [27]. We have a similar hypothesis for SM and ceramides because the homeostasis of these lipids are critical to both the brain and periphery.…”
Section: Discussionmentioning
confidence: 59%
“…CCL, chemokine that contains a C-C motif; CXCL, chemokine that contains a C-X-C motif; G-CSF, granulocyte-colony stimulating factor; GDNF, glialderived neurotrophic factor; ICAM-1, intercellular adhesion molecule-1; IGFBP-1, insulin-like growth factor-binding protein-6; IL, interleukin; PDGF-BB, platelet-derived growth factor BB; TRAIL-R4, TNF-related apoptosis-inducing ligand receptor-4 [15]. Some of these results were verified independently, showing an increased concentration in Biocoll isolated plasma of 5 out of these proteins in MCI and AD patients compared to healthy subjects: EGF, GDNF and MIP1δ (in AD), MIP4 (in MCI), and RANTES (in MCI and AD) [16].…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…While this is likely true, there are cautions that need to be considered with respect to this approach, as well. Among the most promising biomarkers at present include quantitative measures on MRI, cerebrospinal fluid (CSF) markers for tau and Aβ, genetic susceptibilities such as those found with apolipoprotein E genotypes, FDG-PET metabolism patterns, plasma markers for Aβ ratios and proteomic signatures, and molecular imaging such as amyloid imaging with Pittsburgh Compound B (PiB) [10,11,12,13,14,15]. It makes intuitive sense that one or more of these markers coupled with a clinical phenotype may prove very useful.…”
Section: Prediction Modelsmentioning
confidence: 99%